2017
DOI: 10.5812/jjhr.59937
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of miR-155 Expression in the Serum of Patients with Breast Cancer According to Molecular Subtypes of Breast Cancer

Abstract: Background: microRNAs (miRNAs) have been highlighted as potential circulating biomarkers and therapeutic targets for breast cancer (BC). miRNAs have emerged as an extremely promising new class of biomarkers. They have been demonstrated to be remarkably stable in human blood. miR-155 has more than 4 hundred predicted gene targets. The miR-155 plays an essential role in the pathogenesis of breast cancer. The aim of this study was to assess the diagnostic value of miR-155 expression in the serum of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…In this study, the expression of miR-155 in BC patients was 1.68 ± 0.66 times more than that in the control group. This finding was in line with the results of the previous studies that reported increased miR-155 expression by 2.62 to 8.8-fold in breast cancer patients compared to controls [ 16 ]. In the studies of Guo et al [ 15 ], Sun et al [ 17 ], and Zhang et al [ 18 ], the increase in miR-155 expression in BC was 2.94 times, 2.62 times, and 2.87 times, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the expression of miR-155 in BC patients was 1.68 ± 0.66 times more than that in the control group. This finding was in line with the results of the previous studies that reported increased miR-155 expression by 2.62 to 8.8-fold in breast cancer patients compared to controls [ 16 ]. In the studies of Guo et al [ 15 ], Sun et al [ 17 ], and Zhang et al [ 18 ], the increase in miR-155 expression in BC was 2.94 times, 2.62 times, and 2.87 times, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…showed that circulating miR‐140 could be used as a biomarker for breast cancer screening and progression with an AUC of 0.69, a sensitivity of 73% and a specificity of 50% 17 . In another study, miR‐155 had a considerable diagnostic accuracy in patients with molecular subtypes (Luminal A, Luminal B and Triple negative group) of breast cancer 26 . Xu et al 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these markers have low sensitivity and specificity for breast cancer screening. In recent years, aberrant expression of miRNAs has been widely reported in various carcinomas [14][15][16][17][18][19][20][21][22][23]. Half of all known miRNAs have been found in cancer-associated genomic regions or fragile locations, implying that they may have a role in the start and progression of human cancers [27].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are thus potential early diagnostic biomarkers to detect breast cancer and monitor the treatment response of breast cancer patients. Among all uncovered miRNAs, miR-155 is no doubt one of the most attractive ones, which is reported to have potential diagnostic and prognostic value for cancers [14][15][16][17][18][19][20][21][22][23]. As the diagnostic role of miR-155 has not yet been well elucidated and has controversial results, however, we performed a comprehensive meta-analysis and estimated the pooled accuracy of miR-155 for cancer detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation